The Interval Between Preoperative Radiation and Surgery Is Not Associated with Overall Survival for Soft-tissue Sarcomas: An Analysis of the National Cancer Database. Issue 3 (March 2021) - Collier, Christopher D.; Kim, Chang-Yeon; Liu, Raymond W.; Getty, Patrick J.
Abstract: Background: Most cancer centers prefer preoperative radiation therapy (preRT) over postoperative therapy to treat soft-tissue sarcoma (STS) to limit long-term fibrosis, joint stiffness, and edema. Surgery is often delayed after preRT to allow for tissue recovery and to reduce wound complications. However, the association between the time interval between preRT and surgery and survival is unknown. Questions/purposes: (1) What factors are associated with the preRT-surgery interval in patients with STS? (2) Is the preRT-surgery interval associated with overall survival? Methods: The National Cancer Database, a nationwide registry that includes 70% of all new cancers in the United States with 90% follow-up, was reviewed to identify 6378 patients who underwent preRT and surgical resection for a localized extremity or pelvic STS from 2004 to 2014. Patients were excluded if they had lymphatic or metastatic disease at diagnosis (23%; n = 1438), underwent neoadjuvant chemotherapy (24%; 1531), were missing vital status (8%; 487), had chemosensitive histologies (9%; 603), underwent radiation other than external beam (1%; 92), were missing preRT-surgery interval (1%; 45), or had a preRT-surgery interval greater than 120 days (< 1%; 6). A total of 2176 patients were included for analysis, with a mean preRT-surgery interval of 35 ± 16 days. A multiple linear regression model was generated to assess demographic, clinicopathologic, and treatment characteristics associated with the preRT-surgery interval. A Kaplan-Meier survival analysis was then conducted, stratified by the preRT-surgery interval, to assess survival over 10 years. Finally, a multivariate Cox regression analysis model was constructed to further evaluate the association between the preRT-surgery interval and overall survival, adjusted for demographic, clinicopathologic, and treatment characteristics. Results: A longer preRT-surgery interval was associated with higher age (β = 0.002 per year [95% CI 0.0 to 0.004]; p = 0.026), tumor location in the pelvis (compared with the lower extremity; β = 0.15 [95% CI 0.082 to 0.22]; p < 0.001), and malignant peripheral nerve sheath tumor subtype (compared with undifferentiated pleomorphic sarcoma; β = 0.17 [95% CI 0.044 to 0.29]; p = 0.008). A shorter preRT-surgery interval was associated with higher facility volume (β = -0.002 per case [95% CI -0.003 to -0.002]; p = 0.026) and higher tumor stage (compared with Stage I; β = -0.066 [95% CI -0.13 to -0.006]; p = 0.03 for Stage II; β = -0.12 [95% CI -0.17 to -0.065]; p < 0.001 for Stage III). The 5-year overall survival rates were similar across all preRT-surgery interval groups: less than 3 weeks (66% [95% CI 60 to 72]), 3 to 4 weeks (65% [95% CI 60 to 71]), 4 to 5 weeks (65% [95% CI 60 to 71]), 5 to 6 weeks (66% [95% CI 60 to 72]), 6 to 7 weeks (63% [95% CI 54 to 72]), 7 to 9 weeks (66% [95% CI 58 to 74]), and more than 9 weeks (59% [95% CI 48 to 69]). Over 10 years, no difference in overall survival was observed when stratified by the preRT-surgery interval (p = 0.74). After controlling for potentially confounding variables, including age, sex, Charlson/Deyo comorbidity score, histology, tumor size, stage and surgery type, the preRT-surgery interval was not associated with survival (hazard ratio = 1 per day [95% CI 1 to 1]; p = 0.88). Conclusion: With the numbers available, this study demonstrates that a delay in surgery up to 120 days after radiation is not associated with poorer survival. Therefore, clinicians may be able to delay surgery to minimize the risks of wound complications and modifiable comorbidities without affecting overall survival. Level of Evidence Level III, therapeutic study.